Use of ozonated water as an optimizer in the healing process (Research, Society and Development, 2023)
Objective: To emphasize the positive results of the use of medicinal ozone in the treatment of wounds, emphasizing its widespread use in water. Methodology: Integrative review carried out between November 2021 and February 2022, by searching for data in the Virtual Health Library, and in the scientific bases MEDLINE and CAPES. The descriptors used were Ozonated water and Ozone therapy, associated with the filters: full text available; type of document: scientific articles; year of publication 2012 to 2020. The study population comprises 168 documents, 16 of which are used. Results: One of the most recognized actions is germicidal, characterized by the absence of residue, with ozone treatment being preferred in the production of drinking water. Conclusion: It has the ability to activate platelets, inducing growth factors that accelerate healing. It has been proven that the inactivation of bacteria, viruses, fungi, yeasts and protozoa is due to the destruction of their cell envelope through the oxidation of phospholipids and lipoproteins.